PROSPECTS FOR THE DEVELOPMENT OF GASTRONOMIC TOURISM IN UZBEKISTAN: POLITICAL REFORMS, DEMOGRAPHIC REQUIREMENTS AND EXPERIENCE OF "KARIMBEK" RESTAURANT - Umarova Sabina A’zam qizi (Ecominds Press, 2025)
This article analyzes the factors of development of gastronomic orientation in tourism of Uzbekistan, the existing opportunities and prospects. The study highlights the political reforms being carried out in the country to transform tourism into an important sector of the national economy, the need for demographic changes, the need to organize tourism services for the elderly, as well as ways to improve gastronomic services based on the practical activities of the Karimbek restaurant. The article considers international experience, HACCP and Halal standards, digital service, herodietic menus, TOWS analysis, and integration mechanisms of tourism and catering.
Keywords: Gastronomic tourism, national cuisine, digital service, elderly tourism, gerodiet,